COMMUNICATING CSR ON TOURISM INDUSTRY; A PRELIMINARY CASE STUDY OF BALI - Kadek Dwi Cahaya Putra; I Komang Mahayana Putra; A A.A. Mirah Kencanawati (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2019)
As one of the world’s and Indonesia’s most important tourist destination, Bali tourism sector has significantly contributed to both Indonesia’s and Bali’s economy. This study explores how tourism companies communicate CSR including goals, audiences, contents, channels, and strategy. Data are gathered through a single case study approach and thirteen semi-structured interviews to the representatives of hotels, restaurants, tour and travels, and tourism companies in Bali. Data are analyzed by using QDA Miner software. The result shows that relationships, reputation, and branding are the most common goals of communicating CSR. The companies communicated mostly to internal stakeholders; employees and owner, to customers, and the local community. However, there was no specific policy on contents. The companies use reports, meeting, announcement board, e-mail, and in-house communication system to communicate with internal stakeholders; social media, employee, and CSR involvement to communicate with customers; and newspaper, social media, TV, meeting, and employee to communicate to society. An involving strategy was prevalently used mainly through dialogic meeting with the employees and the local community